The history of Kurdish play - پیرباڵ, فەرهاد (Sulaimani Journal for Humanities, 2000)
The history of Kurdish play Since the foundation up to 1908 this scientific research is an attempt of study the Kurdish play history since it's traditional forms in the ancient centuries up to the appearance of the modern play (the European form) at 1919 up to 1958. The Kurdish play appeared under the effect of the Otomanian literary movements which were under the effect of the Western play too at the ends of nineteenth century and the begging of 20th century. The first play Kurdish writer was Abdulrahman Ahmad Hakari who published the first Kurdish play (Mumi Now) in 1919 in the magazine; Zen in Istanbul. At that time, Peramerd; was a student at the college of law in Istanbul too and he could write his first Kurdish texts as well as his first Kurdish play critics. century, the Kurdish play influenced by the Since the twenties of the 20th Arabic Iraqi play and pursued under that effect up to 1958 when produced a critical realism content.